Pesquisa de anticorpos IgG séricos anti-lipoproteínas de mycoplasma fermentans e mycoplasma hominis ou anti-mam (superantigeno de mycoplasma arthritidis) em pacientes com artrite reumatoide ou lupus eritematoso sistemico - Rocha Sobrinho, Hermínio Maurício da (2008)
Rheumatoid Arthritis (RA) and Systemic Lupus Erythematosus (SLE) are autoimmune diseases of unknown etiology. Some species of mycoplasmas cause arthritis in animals and humans, and their lipid-associated membrane proteins (LAMPs) and Mycoplasma arthritidis mitogen (MAM superantigen) are potent stimulators of the immune system. Thus, it has been proposed that mycoplasma can be involved in autoimmune-disease etiology. The objective of the present work was to detect antibodies to MAM and LAMPs of M. hominis and M. fermentans in the patient sera, and to characterize the profile of IgG antibodies reactivity with LAMPs in order to identify the major immunogenic mycoplasmal lipoproteins that could be involved in the etiopathogenesis of these autoimmune diseases. Serum samples were obtained from peripheral blood of female patients at the same age of healthy controls. Recombinant MAM (from M. arthrititidis), LAMPs of M. hominis PG21 and M. fermentans PG18 were used in Western blotting assays. Antibodies to MAM were detected in the patient and control sera (RA: 27.5% vs 18.8%; SLE: 21.7% vs 20.0%). At least 23 LAMPs were found in the preparations of M. hominis PG21 and of M. fermentans PG18 with molecular masses between 20 and 192 KDa. The sera of RA patients recognized a larger number of LAMPs of M. hominis PG21 and M. fermentans PG18 than the control sera (RA: 11 ± 4 vs controls: 7 ± 3, n = 35; p < 0,05). Most of the sera of RA patients presented strong reactivity with LAMPs of M. hominis PG21 (RA: 65.7% vs controls: 20%, p < 0.05). LAMPs of M. hominis PG21 with molecular masses < 49 and ? 20 KDa and LAMPs of M. fermentans PG18 < 102 and ? 58 were mainly recognized by IgG antibodies of RA patients. When comparing sera from SLE patients and controls there was detected no significant differences between the profiles of IgG reactivity. Therefore, M. hominis PG21 LAMPs (< 49 and ? 20 KDa) and M. fermentans PG18 LAMPs (< 102 and ? 58 KDa) are high immunogenic mycoplasmal antigens that can induce antibody cross reactivity with self antigen, contributing with the RA pathogenesis.